Outcome of limb lengthening as a treatment for shortening following successful replantation of traumatic leg amputation: experience with 21 patients - Wu, Caifeng; Liu, Kai; Ren, Shengquan; Liu, Mingming; Ding, Xiaoheng; Yusufu, Aihemaitijiang (Frontiers in Surgery, 2025)
ObjectiveThe purpose of this study was to evaluate the outcomes of limb lengthening based on the Ilizarov technique in the treatment of limb shortening following successful replantation of traumatic lower leg amputation.MethodsThe clinical records and consecutive x-ray photographs of patients with limb shortening deformities following successful replantation of traumatic lower leg amputation treated by limb lengthening using an external fixator were analyzed retrospectively, from January 2012 to December 2022. The demographic data, initial injury, previous treatment, and postoperative data were collected. Paley classification was applied to assess the bone and functional outcomes. The lower extremity functional scale (LEFS), visual analog scale (VAS), and 36-item Short Form Health Survey of life quality (SF-36) were used to evaluate and compare the results of the affected limbs.ResultsA total of 21 patients with a mean age of 42.71 ± 7.96 years, consisting of 17 males (80.9%) and 4 females (19.1%), were successfully treated by limb lengthening using an external fixator. The mean length of limb shortening after limb replantation is 9.93 ± 2.88 cm. The mean external fixation time of this cohort was 16 ± 5.27 months, with a mean external fixation index of 1.59 ± 0.14 month/cm. In bone results, there were 14 cases in excellent, and 6 cases in good, with an excellent and good rate of 95.2%. In functional results, there were 15 cases of excellent, and 5 cases of good, with an excellent and good rate of 95.2%. The knee joint displayed an average over-extension range of motion of 2.9 ± 0.85° (0°–5°), with an average flexion range of 114.7 ± 3.05° (105°–140°). Among the patients, except for the 2 cases of tenodesis, the remaining individuals exhibited an average plantar flexion of 23.2 ± 3.34° (10°–40°) and an average dorsiflexion of 15.1 ± 3.44° (10°–25°). The outcomes of plantar sensation recovery were as follows: 6 cases were classified as S3+, 11 cases as S3, and 4 cases as S2. The LEFS and SF-36 scores followed a characteristic “V”-shaped trajectory, initially declining before subsequently increasing (P < 0.05). VAS scores generally showed a trend opposite to that of the LEFS functional scores (P < 0.05).ConclusionLimb lengthening based on the Ilizarov technique was a safe and effective method for treating shortening following successful replantation of traumatic lower leg amputation, and it could yield satisfactory postoperative bone and functional results. The long treatment period usually associated with this method increases the risk of complications, necessitating good patient compliance with meticulous postoperative management and follow-up guidance to minimize these risks.